Zmiany zawartości różnych form potasu i fosforu w rekultywowanych rolniczo gruntach po eksploatacji kruszywa budowlanego = The changes of various forms of potassium and phosphorus content in the arable soils formed after gravel material exploitation - Drab, Michał; Greinert, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The changes of total and available forms as a result of agricultural remediation of stripping material from gravel pit are presented. The influence of mineral fertilization of ploughing depth were examined, The two amount of potassium and phosphorus. The two factors changed significantly the total amout of potassium and phosphorus. The changes of available forms of K and P were lower.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)